Injury pattern and outcome of road traffic accident victims attending major referral institutions of the Kashmir valley - Bhat, Manzoor Ahmad; Iqbal, Qazi Mohammad (International Journal Of Community Medicine And Public Health, 2020)
Background: Road traffic accidents (RTAs) have emerged as a major global public health problem of this century. WHO global burden of disease study, shows it as the 10th leading cause of death in South-East Asia. In India, according to WHO, road traffic accident is the 6th leading cause of death. The present study aims to assess the magnitude and injury pattern of RTA victims attending three major referral institution of the Kashmir valley. Methods: This prospective observational study was conducted for a period of one year in three major referral institutions of Kashmir valley. Burden of RTA victims was studied from hospital records. For studying detailed injury patterns, the accident victims fulfilling the inclusion criteria and admitted in the wards of these hospitals formed the main study group. Results: RTAs constituted 3% of the total admissions. Most (82.7%) of the studied victims were males. Most (40.3%) of the RTA victims were pedestrians. Head on collision was the most common type of accident (62.9%). 97.6% victims were grievously hurt and head (59.9%) was the most affected part of the body. 88.3% of RTA victims survived while 11.7% died. Conclusions: Young males are the predominant victims of RTAs and head on collision (63%) remains the commonest type of accident. Almost all (97.6%) RTA victims were grievously hurt with 60% having head injuries followed by lower limbs 59.4% and upper limbs 26.8% injuries and 47% victims had multiple injuries.